تقييم الفساد المالي والإداري وأليات مكافحته في الجزائر خلال الفترة (2012-2018) - زارع, رباب; عمامرة, ياسمينة (جامعة الوادي - University of Eloued, 2021)
يهدف البحث الى محاولة تقييم وتشخيص ظاهرة الفساد المالي والإداري في الجزائر ومحاولة إيجاد واقتراح الحلول الجذرية من أجل مكافحته أو التقليل منه، باعتباره ظاهرة تنخر الاقتصاد الوطني وتحد من التنمية الاقتصادية وذلك بالرجوع لأهم مظاهره المنتشرة وكذا أسباب تفشيه وتأثيره على التنمية الاقتصادية الوطنية لمحاولة صياغة اليات مكافحته، والجزائر بوصفها إحدى الدول التي تمر بمرحلة انتقالية إلى اقتصاد السوق قد كانت ولا تزال تعاني لحد الآن من ويلات ظاهرة الفساد المالي والإداري التي أصبحت تنخر مداخيل الدولة خاصة مع غياب المساءلة القانونية وعدم السيطرة على الفساد، في ظل عدم الاستقرار السياسي وعدم تفعيل الحكم الراشد، وغياب التنظيم الإداري. توصل البحث الى أن الجزائر تعاني من استفحال الفساد المالي والإداري بكافة أشكاله وعلى جميع مستوياته، بسبب ضعف أجهزة الرقابة في أداء دورها أو ظهورها شكليا مع إهمال نتائجها، بالرغم من اتخاذ مختلف الإجراءات لمكافحته. تصنيف JEL : D73; L44 Abstract: The research aims to try to evaluate and diagnose the phenomenon of financial and administrative corruption in Algeria and try to find and suggest radical solutions in order to combat it or reduce it, as it is a phenomenon that is eating away at the national economy and limiting economic development by referring to its most widespread manifestations as well as the reasons for its spread and its impact on national economic development to try to formulate mechanisms to combat it And Algeria, as one of the countries that are in transition to a market economy, has been and continues to suffer from the scourge of the phenomenon of financial and administrative corruption that has become a nuisance for the state’s revenues, especially with the absence of legal accountability and lack of control over Corruption, in light of political instability, lack of activation of good governance, and the absence of administrative organization The research found that Algeria is suffering from the aggravation of financial and administrative corruption in all its forms and at all levels, due to the weakness of the oversight bodies in performing their role or appearing formally while neglecting its results, despite taking various measures to combat it.Key words: financial corruption, administrative corruption, transparency, anti-corruption. Jel Classification Codes: D73; L44
Evaluation of financial and administrative corruption and the mechanisms of combating it in Algeria (2012-2018).
Keywords: فساد مالي، فساد اداري، شفافية، مكافحة الفساد.